The Williams collection of Far Eastern ceramics Chinese, Siamese, and Annamese ceramic wares selected from the collection of Justice and Mrs. G. Mennen Williams in the University of Michigan Museum of Anthropology. - Aga-Oglu, Kamer, 1903- (University of Michigan, Museum of Anthropology, 1972)
Kamer Aga-Oglu was curator of the Museum's Asian collections from 1945 to 1974. An extraordinary scholar, Aga-Oglu singlehandedly transformed the study of Asian ceramics, focusing particularly on understudied Asian trade wares in the Museum's collections. She described for the first time a whole new range of East Asian ceramics that until then were unknown, even among specialists, and she documented the pre-European movement of these ceramics throughout the Pacific and as far as Turkey and East Africa. Her catalogs of the Williams Collection contain dozens of photographs and detailed descriptions of the pieces.